The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1093/bmb/ldad001
|View full text |Cite
|
Sign up to set email alerts
|

Implementing brief and low-intensity psychological interventions for children and young people with internalizing disorders: a rapid realist review

Abstract: Introduction Many children fail to receive the mental health treatments they need, despite strong evidence demonstrating efficacy of brief and low-intensity psychological interventions. This review identifies the barriers and facilitators to their implementation. Sources of Data PsycInfo, EMBASE and Medline were searched and a systematic approach to data extraction using Normalization Process Theory highlighted key mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This review’s finding is somewhat at odds with the broader literature examining treatments for adult depression, an evaluation of which reveals strong supporting evidence for brief, low-intensity (LI) psychological interventions, particularly in the context of collaborative care and stepped-care models [ 49 ]. LI psychological interventions, abbreviated versions of evidenced-based therapies that can be delivered by workers with little to no formalized mental health training, are generally limited in terms of duration and frequency of contact (e.g., <6–10 distinct sessions) [ 50 , 51 ]. Numerous systematic reviews and meta-analyses have demonstrated the effectiveness of LI interventions for treating a range of mental health conditions [ 38 , 43 , 52 , 53 ], and their integration with stepped-care treatment models have been encouraged by the Lancet Commission for Global Mental Health and Sustainable Development as well as the WHO Mental Health Gap Action Plan [ 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review’s finding is somewhat at odds with the broader literature examining treatments for adult depression, an evaluation of which reveals strong supporting evidence for brief, low-intensity (LI) psychological interventions, particularly in the context of collaborative care and stepped-care models [ 49 ]. LI psychological interventions, abbreviated versions of evidenced-based therapies that can be delivered by workers with little to no formalized mental health training, are generally limited in terms of duration and frequency of contact (e.g., <6–10 distinct sessions) [ 50 , 51 ]. Numerous systematic reviews and meta-analyses have demonstrated the effectiveness of LI interventions for treating a range of mental health conditions [ 38 , 43 , 52 , 53 ], and their integration with stepped-care treatment models have been encouraged by the Lancet Commission for Global Mental Health and Sustainable Development as well as the WHO Mental Health Gap Action Plan [ 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that a lack of adequate training resources is a possible factor contributing to implementation challenges of low intensity psychological interventions for children and young people [ 31 ]. To address this issue, the current project has delivered training on low intensity psychological interventions for CYP in the context of LTCs for clinicians from participating hospitals [ 32 ].…”
Section: Methodology: Participants Interventions and Outcomesmentioning
confidence: 99%
“…All students individually solved the same three problems, spending approximately 15 min of class time on each task. The use of quasi‐experimental brief interventions has been seen in educational research (e.g., Lin & Powell, 2023; Strunk, 2012; Wisman et al, 2019) and is more common in psychological research, for example, in the treatment of self‐injurious behaviors (see Dobias et al, 2023 for a review), substance abuse (Center for Substance Abuse Treatment, 1999), and anxiety and depression (see Roach et al, 2023 for a review). For the control section, the instructor simply handed each student the problem statement sheet.…”
Section: Methodsmentioning
confidence: 99%